2016
DOI: 10.1097/md.0000000000004206
|View full text |Cite|
|
Sign up to set email alerts
|

Is cerebral glucose metabolism related to blood–brain barrier dysfunction and intrathecal IgG synthesis in Alzheimer disease?

Abstract: The aim of this study was to investigate the relationships between blood–brain barrier (BBB) dysfunction, intrathecal IgG synthesis, and brain glucose consumption as detectable by means of serum/cerebrospinal fluid (CSF) albumin index (Qalb) and IgG index [(CSF IgG/serum IgG) × Serum albumin/CSF albumin)] and 2-deoxy-2-(18F) fluoro-d-glucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) in a selected population affected by Alzheimer disease (AD). The study included 134 newly diagnosed AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…As well as occurring with insulin signaling, it has been found that impairment of cerebral glucose metabolism could occur in the early stages of AD, and deteriorate with the progression of the disease (Shah, Desilva, & Abbruscato, ; Chen, Deng, Zhang, & Gong, ). Compared to peripheral organs, the availability of glucose and other nutrients for neural tissues is limited by the dynamic restrictive properties of the BBB (Chiaravalloti et al, ; Keeney, Ibrahimi, & Zhao, ). Because neurons are unable to synthesize or store glucose, they are completely dependent on glucose transport across the BBB, which is facilitated by glucose transporters (GLUTs) and sodium‐dependent glucose transporters (secondary active transport; SGLT), each with different kinetic properties.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…As well as occurring with insulin signaling, it has been found that impairment of cerebral glucose metabolism could occur in the early stages of AD, and deteriorate with the progression of the disease (Shah, Desilva, & Abbruscato, ; Chen, Deng, Zhang, & Gong, ). Compared to peripheral organs, the availability of glucose and other nutrients for neural tissues is limited by the dynamic restrictive properties of the BBB (Chiaravalloti et al, ; Keeney, Ibrahimi, & Zhao, ). Because neurons are unable to synthesize or store glucose, they are completely dependent on glucose transport across the BBB, which is facilitated by glucose transporters (GLUTs) and sodium‐dependent glucose transporters (secondary active transport; SGLT), each with different kinetic properties.…”
Section: Alzheimer Diseasementioning
confidence: 99%
“…Alzheimer disease (AD) is the most common cause of dementia and cognitive disorders and is one of the most important causes of morbidity and mortality among the aging population [ 17 ]. It is characterized by extracellular senile plaques of A β peptides and intracellular neurofibrillary tangles of tau protein [ 18 , 19 ]. Diverse factors have been related to AD development, but OS and inflammation invariably are involved [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, data concerning the relationship between glucose metabolism and common neuropsychological assessment are poor, even if the results of the neuropsychological tests may be considered as statistical parameters in research papers that include brain data analysis, by using computer-aided metrics such as statistical parametric mapping (SPM) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%